Neutralization Acid Mine Drainage (AMD) using NaOH at PT. Jorong Barutama Grestone, Tanah Laut, South Borneo - Umi Baroroh Lili Utami; Heru Susanto; Bambang Cahyono (Universitas Islam Indonesia, 2020)
Acid mine drainage (AMD) is mine water with a low pH derived from the oxidation of pyrite containing sulfide with water and air to produce sulfide acid (H2SO4) containing free sulfate. Acid mine drainage treatment carried out at PT Jorong Barutama Greystone Tanah Laut uses limestone at a cost of Rp.220. - per cubic meter of water. This study was conducted to determine the use of technical NaOH for changes in mine acid quality (pH. Fe and Mn). The method carried out by active handling is by adding technical NaOH into mine acid water. The results showed that neutralization of acid mine drainage using technical NaOH 10% to pH 8. was able to reduce Fe by 18.60 - 25.42% and Mn by 31.95 - 39.27%. at a cost of Rp.327. - per meter cubic of water